2013
DOI: 10.1177/0885066613491919
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Mortality of the Acute Respiratory Distress Syndrome on Admissions of Patients With Ischemic Stroke in the United States

Abstract: Our analysis demonstrates that ARDS is rare after AIS. Despite an overall significant reduction in mortality after AIS, ARDS carries a higher risk of death in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…ARDS was also associated with a significant increase in mortality, and it prolonged the duration of mechanical ventilation and the length of ICU stay. Similarly, in previous reports, ARDS has been identified as a major contributor to the morbidity and mortality of patients with brain injuries [2,3,5,15,17,18,30]. ARDS also worsens longterm neurologic outcome [1,2,3,32], and is associated with longer ICU and hospital length of stay [5,29].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…ARDS was also associated with a significant increase in mortality, and it prolonged the duration of mechanical ventilation and the length of ICU stay. Similarly, in previous reports, ARDS has been identified as a major contributor to the morbidity and mortality of patients with brain injuries [2,3,5,15,17,18,30]. ARDS also worsens longterm neurologic outcome [1,2,3,32], and is associated with longer ICU and hospital length of stay [5,29].…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have shown ARDS to be a consequence of underlying illness and predisposing conditions such as young age, male gender, ethnicity, history of chronic arterial hypertension, diabetes, chronic obstructive pulmonary disease, development of sepsis, cardiovascular, renal and haematological dysfunctions [17,30,31]. In addition, other interventions such as exposure to blood products may potentiate pulmonary injury in a susceptible host or lead directly to transfusion-related ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed these factors with variable results. [11415161718192021222324252627] The aims of this study were to determine the role of demographic data such as age, gender, and race on the outcome and also to study other variables that have not been previously addressed such as pre-ICU patient location and type of ICU.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the risk of death from ARDS associated with sepsis and burn were higher than with trauma or neurological complications. [252627]…”
Section: Discussionmentioning
confidence: 99%
“…The definition for ARDS using administrative data we used has been widely utilized in many other studies(Reynolds et al, 1998; Rincon et al, 2014, 2012; Rush et al, 2016; Veeravagu et al, 2014). Our definition of ARDS was consistent with previous authors and included (1) International Classification of Diseases, Ninth Revision (ICD −9) codes for acute respiratory failure following trauma and surgery (518.51); (2) other pulmonary insufficiency, not elsewhere classified, following trauma and surgery (518.52); (3) acute and chronic respiratory failure following trauma and surgery (518.53); (4) acute respiratory failure (518.81); (5) and other pulmonary insufficiency, not elsewhere classified (518.82)(Reynolds et al, 1998; Rincon et al, 2014; Veeravagu et al, 2014). Unfortunately, due to the lack of detailed granular variables in the NIS dataset we were unable to classify patients according to the Berlin definition of ARDS(Ferguson et al, 2012).…”
Section: Methodsmentioning
confidence: 99%